A processing product of the Plasmodium falciparum reticulocyte binding protein RH1 shows a close association with AMA1 during junction formation - Gunalan, Karthigayan (2021)
Plasmodium falciparum responsible for the most virulent form of malaria invades human erythrocytes through multiple ligand-receptor interactions. The P. falciparum reticulocyte binding protein homologues (PfRHs) are expressed at the apical end of merozoites and form interactions with distinct erythrocyte surface receptors that are important for invasion. Here using a range of monoclonal antibodies (mAbs) against different regions of PfRH1 we have investigated the role of PfRH processing during merozoite invasion. We show that PfRH1 gets differentially processed during merozoite maturation and invasion and provide evidence that the different PfRH1 processing products have distinct functions during invasion. Using in-situ Proximity Ligation and FRET assays that allow probing of interactions at the nanometre level we show that a subset of PfRH1 products form close association with micronemal proteins Apical Membrane Antigen 1 (AMA1) in the moving junction suggesting a critical role in facilitating junction formation and active invasion. Our data provides evidence that time dependent processing of PfRH proteins is a mechanism by which the parasite is able to regulate distinct functional activities of these large processes. The identification of a specific close association with AMA1 in the junction now may also provide new avenues to target these interactions to prevent merozoite invasion.